2010
DOI: 10.1021/es103314n
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Radioiodine Plume Increasing in Concentration at the Savannah River Site

Abstract: Field and laboratory studies were carried out to understand the cause for steady increases in (129)I concentrations emanating from radiological basins located on the Savannah River Site, South Carolina. The basins were closed in 1988 by adding limestone and slag and then capping with a low permeability engineered cover. Groundwater (129)I concentrations in a well near the basins in 1993 were 200 pCi L(-1) and are presently between 400 and 1000 pCi L(-1). Iodine speciation in the plume contained wide ranges of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…S1). The larger plate-like crystals are likely hematite, which is frequently reported in these soils (Kaplan et al, 2011), was detectable by XRD in some of the bulk soils (Table 1), and also identified by Mössbauer spectroscopy (Fig. 4).…”
Section: Particle Morphology In the Rhizosphere Versus Non-rhizospherementioning
confidence: 68%
“…S1). The larger plate-like crystals are likely hematite, which is frequently reported in these soils (Kaplan et al, 2011), was detectable by XRD in some of the bulk soils (Table 1), and also identified by Mössbauer spectroscopy (Fig. 4).…”
Section: Particle Morphology In the Rhizosphere Versus Non-rhizospherementioning
confidence: 68%
“…Indeed, as previously shown by Reiller and Moulin (2003), Schlegel et al (2006) and Steinberg et al (2008), the iodination of the organic matter leads to the formation of covalent bonds, thus, to an immobilisation of iodine. Such a mechanism is capable of explaining the retardation of the iodide migrating through soils made of relatively fresh and reactive organic matter (see e.g., Kaplan et al, 2011;Zhang et al, 2011). However, extra cautions have to be taken for indurated clay rocks, in which NOM are kerogen-type, known to be mature and relatively inert (Deniau et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The highest concentration reported to date, 1060 pCi/L, was in 1996 for a well adjacent to the largest basin. Concentrations of 129 I in this well have been rising over the past twenty years, while concentrations of most other radionuclide contaminants have been decreasing (Kaplan et al., 2011). The increase likely reflects release of adsorbed 129 I from vadose zone and seepage basin sediments as pH has risen with time (Denham and Vangelas, 2008; Kaplan et al., 2011).…”
Section: Radioiodine Sourcesmentioning
confidence: 99%